Double-sided friction stir welding of 2195 aluminum-lithium alloy - SUN Shouyi; WANG Jin; CAO Gaowei; MU Kaicheng (Cailiao gongcheng)
Based on the response surface design， the optimal process parameters for single-side friction stir welding（FSW） of 2195 Al-Li alloy sheets are studied. It is found that the higher the rotation speed and the lower the welding speed， the higher the tensile strength of the welded joint. The results show that in the single-side FSW， when the pin length is 2/3 length of the thickness of the plate， the root of the weld appears unwelded defects， the fracture form of the welded joint is between brittle and plastic fracture， and the tensile strength of the joint is poor. Based on the optimum process parameters of single-sided welding， double-sided FSW can overcome the unwelded defects at the root of single-sided welding. Under different tool pressures， when the stirring head speed is 1600 r/min， the feed speed is 150 mm/min， and the pressure is 0.1 mm， the double-sided welding can improve the tensile strength of the welded joint by about 10% and the elongation of the welded joint by 10%. In two-sided FSW， the material flow on the forward side is obvious， and the fracture mode of the welded joint is a plastic fracture. In double-sided welding， the plate is subjected to secondary stirring and heating， resulting in increased softening of the material in the welding area.The microhardness of the double-sided welded joint is further reduced than that of the single-sided welding.